2020
DOI: 10.1007/s40200-020-00643-9
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of healthcare workers in the COVID-19 pandemic: A systematic review

Abstract: Purpose The novel coronavirus 2019 (COVID-19) is widely spreading all over the world, causing mental health problems for most people. The medical staff is also under considerable psychological pressure. This study aimed to review all research carried out on the mental health status of health care workers (HCWs) to bring policymakers and managers' attention. Methods A literature search conducted through e-databases, including PubMed, EMBASE, Scopus, and Web of Science (WoS) from December 2019 up to April 12th 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
509
8
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(676 citation statements)
references
References 50 publications
63
509
8
21
Order By: Relevance
“…Sethi et al (2020), in a qualitative study with Pakistani healthcare workers (physicians: n = 237 and dentists: n = 35), Shechter et al (2020), in a New York hospital study (nurse: n = 313 and physicians: n = 344), and Salazar de Pablo (2020), in a systematic review reported an impact of the pandemic on mental (insomnia, psychological distress, anxiety, and depressive symptoms), physical (cough, fatigue, fever, headaches, and sore throat), social health, and well-being. Similar findings were also reported in other systematic reviews that include studies from China, Singapore, Italy, Iran, and Spain (Luo et al 2020;Muller et al 2020;Pappa et al 2020;Vizheh et al 2020). However, as far as we know, there are no data related to psychological symptoms from the pandemic in Brazilian healthcare workers that can be compared with the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sethi et al (2020), in a qualitative study with Pakistani healthcare workers (physicians: n = 237 and dentists: n = 35), Shechter et al (2020), in a New York hospital study (nurse: n = 313 and physicians: n = 344), and Salazar de Pablo (2020), in a systematic review reported an impact of the pandemic on mental (insomnia, psychological distress, anxiety, and depressive symptoms), physical (cough, fatigue, fever, headaches, and sore throat), social health, and well-being. Similar findings were also reported in other systematic reviews that include studies from China, Singapore, Italy, Iran, and Spain (Luo et al 2020;Muller et al 2020;Pappa et al 2020;Vizheh et al 2020). However, as far as we know, there are no data related to psychological symptoms from the pandemic in Brazilian healthcare workers that can be compared with the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In July 2020, when the drafting of this text began, there were only five studies reporting data related to the subject: one from Spain (SantamarĂ­a et al 2020 ), one from Pakistan (Sethi et al 2020 ), two from China (Lai 2020 ; Zhang et al 2020 ), and one with dentists from the Middle East (Ahmed et al 2020 ). After a review in December 2020, a higher number of studies were found, including five systematic reviews (Luo et al 2020 ; Muller et al 2020 ; Pappa et al 2020 ; Salazar de Pablo et al 2020 ; Vizheh et al 2020 ) that indicate high risk for mental problems of such workers, especially sleep disorders, depression, anxiety, stress, and overall psychological impact due to the pandemic. The studies that compared different work categories (Lai 2020 ; Luo et al 2020 ; Pappa et al 2020 ; Shechter et al 2020 ; Vizheh et al 2020 ) found that nurses had more symptoms than physicians.…”
Section: Introductionmentioning
confidence: 99%
“…As a secondary consequence, the SARS-CoV-2 pandemic has instigated a mental health crisis among the world’s population. Indeed, numerous reports have described high prevalence (condition-dependent ranges of 12% – 67.5%) of anxiety and depressive symptoms as well as insomnia and the presence of emotional trauma among clinical care providers and essential workers [ [170] , [171] , [172] ]). Among the general population, the social isolation, uncertainty and low locus of control induced by global lockdowns is a very likely explanation for the observed up-tick in patients seeking mental health treatment and presenting with mood dysregulation.…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…Previous national and international studies, however, have shown high levels of stress among HCWs, whether in regular conditions or during the COVID-19 pandemic [6,[11][12][13][14][15]. For example, the Middle East Respiratory Syndrome coronavirus (MERS-CoV) has been identified in 2012 in many countries worldwide and most cases were diagnosed in Saudi Arabia [16].…”
Section: Introductionmentioning
confidence: 99%